Proceso atención de enfermería en paciente con traumatismo craneal. - Patín García, Jerson Daniel (2022)
The present study was carried out in a full-term male patient with head trauma. Head trauma is an alteration in brain function or other evidence of brain pathology, caused by an external force, which may consist of a direct impact on the brain. skull, rapid acceleration or deceleration, penetration of an object, or shock waves from an explosion, with the presence of at least one of the following: altered consciousness or amnesia, neurological or neurophysiological changes, diagnosis of skull fracture or injury intracranial and occurrence of death as a final result of trauma. The damage suffered by the brain after a traumatic brain injury is due, on the one hand, to the primary injury (contusion) directly related to the impact on the skull or to the rapid acceleration/deceleration movement, and on the other hand, to the secondary injury (edema, hemorrhage, increased pressure in the skull, etc.) that develops as a result of the primary injury during the first days after the accident and that can have serious consequences on the functional prognosis.